First Report of the HEV Seroprevalence and the Risk Factor Assessment in the West Bank, Palestine, during the Period of 2015–2017 - Kamal Dumaidi; Alaa M. Abudamous; Rasmi Abu-Helu; Hanan Al-Jawabreh; Yazan Dumaidi; Amer Al-Jawabreh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Hepatitis E virus is emerging viral hepatitis with hyperendemicity in many countries. Data on the burden of disease is not available in Palestine. This study aims to determine the seroprevalence and the risk factors of the HEV among the general population of the West Bank, Palestine. In this cross-sectional study, a total of 432 sera samples from 40 localities in the eleven districts of the West Bank and Jerusalem, Palestine, during the period of March 2015 to March 2017, were tested for HEV-IgG. A structured questionnaire was used to collect data of the participants’ demographics and disease risk factors. The overall seroprevalence was 3.7%. Level of education was significantly inversely associated with HEV seropositivity (P=0.04). Purely spatial analysis did not detect any significant cluster related to the distribution of HEV-IgG cases; however, living in the southern West Bank is shown to be significantly associated with HEV. Age was also associated with HEV seropositivity. The young (<19 years) and adults (>40 years) had the highest prevalence, compared to those between 20 to 39 years old (P=0.12). Furthermore, males and those in contact with animals were associated with HEV seropositivity (P=0.1 and 0.3, respectively). In conclusion, the seroprevalence of HEV IgG in the West Bank, Palestine is low. Several well-investigated risk factors cannot be supported by our results due to the small number of the positive HEV-IgG samples. Finally, this study is useful for providing a first look into the seroepidemiology of HEV in Palestine.